2005
DOI: 10.1029/2004jd005580
|View full text |Cite
|
Sign up to set email alerts
|

Variability of active chlorine in the lowermost Arctic stratosphere

Abstract: [1] We examine the variability of ClO in the Arctic upper troposphere and lowermost stratosphere (UTLS) during the winter of 1999-2000. Data are binned relative to NO y , a species that is a proxy for photochemical age and a photochemical source of NO x . Enhancements in the [ClO]/[Cl y ] ratio relative to values expected from gas-phase chemistry alone were observed throughout the region and were largest in the coldest sampled regions, where T < 208 K. At low NO y values, where particles containing NO y and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…While changes in transport in the lowermost stratosphere could explain at least part of the observed trend (Fusco and Salby, 1999;Salby and Callaghan, 2004;Hood and Soukharev, 2005), chemical ozone loss due to halogen chemistry is also thought to play a significant role (Salawitch et al, 2005;Solomon et al, 1997). Besides higher than previously suggested and still slightly increasing amounts of bromine in this region (Dorf et al, 2006), catalytic ozone destruction by ClO produced as a result of heterogeneous chlorine activation on sulphate aerosol and on ice-particles in cirrus clouds has been suggested (Borrmann et al, 1996Bregman et al, 2002;Keim et al, 1996;Solomon et al, 1997;Thornton et al, 2003Thornton et al, , 2005.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…While changes in transport in the lowermost stratosphere could explain at least part of the observed trend (Fusco and Salby, 1999;Salby and Callaghan, 2004;Hood and Soukharev, 2005), chemical ozone loss due to halogen chemistry is also thought to play a significant role (Salawitch et al, 2005;Solomon et al, 1997). Besides higher than previously suggested and still slightly increasing amounts of bromine in this region (Dorf et al, 2006), catalytic ozone destruction by ClO produced as a result of heterogeneous chlorine activation on sulphate aerosol and on ice-particles in cirrus clouds has been suggested (Borrmann et al, 1996Bregman et al, 2002;Keim et al, 1996;Solomon et al, 1997;Thornton et al, 2003Thornton et al, , 2005.…”
Section: Introductionmentioning
confidence: 90%
“…This seems quite realistic, because the low temperatures prevalent in the TTL will lead to relatively high heterogeneous reaction rates. Indeed, the highest degree of chlorine activation -given by the x(ClO)/x(Cl y ) ratio following Thornton et al (2003) -was found in air masses with low ozone but also very low temperatures (Fig. 4), where heterogeneous reactions are most likely to play a relevant role.…”
Section: Individual Case Study Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could potentially increase the OClO columns. Thornton et al (2003Thornton et al ( , 2005 report measurements of ClO in the lowermost stratosphere at high latitude regions. They suggest heterogeneous chlorine activation on cold particulate surfaces as water-rich background aerosols containing sulphate and nitrate.…”
Section: Discussionmentioning
confidence: 99%